Simulation of hydrodynamics pressure to determine the value of Von-mises stress,displacement and strain of the geotube - Nur Izzati Binti Mohd Razi; MUHAMMAD AI'MULLAH BIN ABDULLAH (Progress in Engineering Application and Technology, 2023)
; This study focuses on modeling, simulating and analyzing geotube structures under hydrodynamic pressure changes where the materials have been provided by My Flexitank Industry (MYF) Sdn. Bhd. namely linear lowdensity polyethylene (LLDPE). Dewatering process is excess water drains out of the porous geotextile layer of the Geotube where this process takes a long time to complete and increase cost. The objective of this research is to model the geotube structure according to diameter given by MY Flexitank Industry (MYF) Sdn. Bhd. and calculate and obtain the maximum value of Von-Mises stress, displacement and strain using Solidwork 2021 software. Therefore, Linear low-density polyethylene (LLDPE) Plastic material is the material used for new material for geotube. Changing the dewatering to non-dewatering process of the geotube need more research to obtain the good result. From the data result, the value obtain from the simulation is not more than the LLDPE properties theoretical value. Based on the results, it may be concluded that the geotube did not fail or burst during the simulation when the pressure applied. However, another engineering design tool, such as ANYSYS or ABACUS software, can be used to acquire a more precise result value.